New academic building : final environmental impact statement : University of Wisconsin-La Crosse, La Crosse, Wisconsin : state project no. 0513O - Buchli, Lisa; Johnson, Dennis L.; Wisconsin. Division of State Facilities (Ayres Associates, 2008)
Alternate titles: New academic building, University of Wisconsin-La Crosse; Final environmental impact statement
Keywords: University of Wisconsin-La Crosse -- Buildings